Pengenalan Rumput Mulato sebagai Potensi Sumber Hijauan Sapi Perah di Kelompok Peternak Tunas Mekar, KSU Tandangsari, Sumedang - Novi Mayasari; Lia Budimulyati Salman; Iin Susilawati; Apong Sandrawati; Muhammad Rifqi Ismiraj (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
The Tunas Mekar Farmer Group (TMFG) is a group of farmers belong to dairy farming cooperation (KSU) Tandangsari with the commodity of Friesian Holstein (FH) dairy cattle whose business objectives are to produce cow's milk and breeding of dairy cows. One of the problems that may have caused the low milk production was the result of the low quality and availability of the forage provided by the KPTM members. It is necessary to look for forage alternatives that have advantages in biomass and protein and fiber content, in the hope that it can help meet the nutritional needs of livestock. One of the forages that has advantages in protein and fiber content is mulato grass (Brachiaria hybrid cv. Mulato) which is reported to have the ability to live in a good dry season, easy to breed through tillers, and quite high palatability by ruminants. This community service is carried out to introduce and disseminate the potential benefits of mulato grass as a potential forage source for dairy cows. Community service activities are carried out with the exploratory stage, then the extension stage, and followed by the mentoring stage using an online platform (Whatsapp group). Community service activities regarding the potential of mulato grass as a forage for dairy cows were successfully implemented. With the enthusiasm of extension participants, extension activities can increase the insight of farmers participating in the extension, reflected in the success of farmers in planting and cultivating mulato grass.